Dialectic of Myth and Enlightenment: Rethinking Scientific Progress and Humanity through The Shape of Water - Mala Hernawati (Universitas Gadjah Mada, 2020)
Since the Scientific Revolution, the clash between myths, science, and humanity has been a recurring theme found in literary works. In the midst of today’s rapid, massive, and disruptive technological development, Guillermo del Torro and Daniel Kraus collaboratively present a historical fantasy novel, The Shape of Water, which features the issues of scientific progress and humanity in a romance between a mute lower-class woman Elisa Esposito and a mystical amphibian creature from South America, Deus Brânquia. The novel portrays Deus Brânquia as an experimental asset of the American government to be studied for the Cold War military advancement. This study aims to analyze the representation of destructive science in the novel and examine the demythologization of Deus Brânquia as a depiction of Enlightenment's impact on the modern worldview. Using critical theory on the dialectic of myth and enlightenment proposed by Max Horkheimer and Theodor W. Adorno, this study finds that The Shape of Water articulates a cynical notion to Enlightenment’s legacy as it portrays how the progress of modern science can lead to horrific domination upon the marginalized human and nonhuman creature.